Prevalencia de hematuria enzoótica bovina por medio de tiras reactivas en el cantón Piñas - Ramírez Ramírez, Cristian Michael (2012)
This research was conducted in the canton Piñas, in 2012, in order to determine the prevalence of bovine enzootic hematuria, which was performed by using dipstick urinalysis. To make this work we investigated a total of 600 animals in 32 herds of Canton Piñas. Realize yourselves Studies found that the prevalence of bovine enzootic hematuria is 9.83%.